PCNA, Ki-67, p53, bcl-2 and Prognosis in Intraoral Squamous Cell Carcinoma of the Head and Neck - Karin Nylander; Elsy‐Britt Schildt; Mikael Eriksson; Göran Roos (Analytical Cellular Pathology)
Eighty patients with primary intraoral squamous cell carcinomas of the head and neck, with a follow‐up of 4–14 years were analysed for clinical outcome in relation to immunohistochemical expression of PCNA, Ki‐67, p53, bcl‐2 and presence of mutations in the p53 gene. The tumour site was not associated with the different parameters calculated. PCNA and Ki‐67 labelling showed median values of 56% and 32%, respectively, and neither antigen was of predictive value. Fiftyfive percent of the tumours expressed p53, and 38 (48%) had mutations in the p53 gene. No association between the presence of p53 protein or mutations in the p53 gene and clinical outcome was found. Bcl‐2 positivity was detected in a minor fraction (10%) of the tumours.